Zasebno je politično - Kanjuo-Mrčela, Aleksandra (Teorija in praksa, 2012)
We assume that specific everyday practices in the field of politics in Slovenia are based on the traditionally defined gender roles of men and women in private and public life, that they reinforce these roles, as well as hinder the equal participation of men and women in politics. The analysis of interviews with male and female politicians active at the national level shows the existence of a gender contract that operates at the level of expectations as well as actual practices and which results in an asymmetrical load of private life responsibilities of men and women in politics. The political profession in Slovenia is highly masculinised. Female and male politicians adapt to the existing structure which does not consider the benefits of the coordination of their private and professional lives.
Keywords: Političarke; Women politicians; Politiki; Politicians; Delitev dela po spolu; Sexual division of labor; Work and family; Delo in družina; Gospodinjsko delo; Housework; Slovenia; Slovenija; politics; politika; poklicni razvoj